6z-3(z+8)=9

Simple and best practice solution for 6z-3(z+8)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6z-3(z+8)=9 equation:


Simplifying
6z + -3(z + 8) = 9

Reorder the terms:
6z + -3(8 + z) = 9
6z + (8 * -3 + z * -3) = 9
6z + (-24 + -3z) = 9

Reorder the terms:
-24 + 6z + -3z = 9

Combine like terms: 6z + -3z = 3z
-24 + 3z = 9

Solving
-24 + 3z = 9

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 3z = 9 + 24

Combine like terms: -24 + 24 = 0
0 + 3z = 9 + 24
3z = 9 + 24

Combine like terms: 9 + 24 = 33
3z = 33

Divide each side by '3'.
z = 11

Simplifying
z = 11

See similar equations:

| 6x-5xy+6x=0 | | 9w^2+15w^3= | | 2a+7=2a | | 5y-1=34 | | 3.6+10m=6.49 | | 183-x=8x | | 8x-4=9x-2 | | 107x-31x=4677 | | 30=x-40 | | E+e+e+e+e+e= | | 3x+3-5=5x-2 | | 2c+8=3c+10 | | 4.6+10m=7.45 | | 5x+10=8x+7 | | (6x+7)(x-3)=0 | | 2(5x-8)+2=2(x-5) | | 0=16t^2-17t-217 | | 5x+3=x+349 | | 5z+5z+4z+3z+3z=540 | | x+6-2x=2x-8 | | 9z+z=6z-5-3z | | 4(x+1)=5x-2x+4 | | -x-4=2x+5 | | 66a-8a+7a-57a+11a=95 | | x-1=(4(x+2)) | | 5s-2s-2s+s-2=54 | | 0=5t^2+5t-25 | | 3r^2+375=0 | | x+5+14=180 | | 5(x-2)-4(5x-1)=-16(x+1)+5 | | 8x=15x-63 | | x-3=4(x+2) |

Equations solver categories